A lifetime burning in every moment from the journals of Alfred Kazin - Kazin, Alfred 1915-1998 (HarperCollins, 1996)
While leading an active life, Kazin has faithfully kept diaries from the late 1930s up to the present. A Lifetime Burning in Every Moment offers readers the best of thousands of pages of his journals, comprising an extraordinary picture of intellectual, social, political, and even celebrity life - including such figures as Bernard Berenson, Josephine Herbst, Saul Bellow, Bernard Malamud, Hannah Arendt - during the past five and a half decades. Kazin candidly reflects on his four marriages, his feelings about the Holocaust, his criticism of American society, the pleasure and stimulation of reading good writers (Simone Weil, Ignazio Silone, Joseph Conrad, and Saul Bellow, among others), his need to pray, his travels abroad and within the United States, and more.
Keywords: Kazin, Alfred <1915-1998> -- Diaries; Critics -- United States -- Biography; USA; Biografie; Tagebuch